FAMILY AS CHILDREN'S FIRST EDUCATION; THE ROLE OF PARENTS IN THE DEVELOPMENT OF ISLAMIC RELIGIOUS EDUCATION FOR ELEMENTARY SCHOOL AGE CHILDREN - Muhammad Rizaq (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2022)
This research is motivated by the condition that the Indonesian nation is currently facing serious challenges, especially in the context of education because it has to deal with global competition, information and technology. The busyness of parents in their activities outside the home makes less attention to the role in the development of Islamic religious education for elementary school-aged children, which of course really needs an example from parents. Elementary school age children (SD) are those aged 7-12 years, in the following phase marked by everything having to go through coercion. Under pressure from adults or those in power, children exert little moral or logical control over their behavior. Age 12 and over (heteronon stage), in this phase a child begins to understand values ​​and begins to interpret in his own way. Morality is characterized by cooperation, not coercion, interaction with peers, discussion, self-criticism, a sense of equality and respect for others are the main factors in this phase. The family as the first school concept for children, plays an important role in the development of children's Islamic religious education. Exemplary, good habits are part of inculcating noble character and positive things that parents can do as first teachers for children. Fathers and mothers who have strong visions and missions strive to provide tarbiyah (education) in the form of recitations, literacy, as well as tazkiyah (self-cleaning) processes. each family member has a special worship charity, superior, both ritually and socially by making a family da'wah schedule and agenda. Penelitian ini dilatarbelakangi oleh kondisi bangsa Indonesia saat ini sedang dalam menghadapi tantangan yang berat terutama dalam konteks pendidikan karena harus berhadapan dengan global competition, information and technology. Kesibukan orangtua dalam aktivitasnya diluar rumah menjadikan berkurangnya perhatian akan peran dalam perkembangan pendidikan agama Islam untuk anak usia sekolah dasar yang tentunya sangat membutuhkan keteladanan dari orangtua. Anak usia sekolah dasar (SD) adalah mereka yang berusia 7-12 tahun, pada fase berikut ditandai dengan segala sesuatu harus melalui paksaan. Dibawah tekanan orang dewasa atau orang berkuasa, anak sedikit menggunakan kontrol moral dan logika terhadap perilakunya. Usia 12 keatas (tahap heteronon), pada fase berikut seorang anak mulai mengerti nilai-nilai dan mulai memaknai dengan caranya sendiri. Moralitas ditandai dengan kooperatif, bukan faktor paksaan, interaksi dengan teman sebaya, diskusi, kritik diri, rasa persamaan dan menghormati orang lain merupakan faktor utama pada fase ini. Keluarga sebagai konsep sekolah pertama bagi anak, berperan penting bagi perkembangan pendidikan agama Islam anak. Keteladanan, pembiasaan baik merupakan bagian penanaman akhlak mulia dan hal positif yang dapat dilakukan orangtua sebagai guru pertama bagi anak. Ayah dan ibu yang memiliki visi-misi kuat berupaya untuk memberikan tarbiyah (pendidikan) dalam bentuk tilawah, literasi, juga proses tazkiyah (pembersihan diri), dan taklim. setiap anggota keluarga memiliki amal ibadah khusus, unggulan, baik secara ritual juga sosial dengan dibuatkannya jadwal dan agenda dakwah keluarga.